PENGARUH REPUTASI DAN PEMASARAN MEDIA SOSIAL TERHADAP DAYA SAING UNIVERSITAS KATOLIK SANTO THOMAS MEDAN - Tarigan, Immanuel; Haloho, Elizabeth; Padang, Novi Natalia; Purba, Imelda Rimenda (UNIKA Santo Thomas, 2023)
The purpose of this study was to find out and analyze reputation which influences competitiveness, social media marketing influences competitiveness, and reputation and social media marketing simultaneously influence competitiveness of Santo Thomas Catholic University of Medan. The research method used is a quantitative descriptive research method. The population in this study were all active students in the 2022/2023 Academic Year, totaling 6,540 people. The technique for determining the sample in this study used Propotionate Stratified Random Sampling. As for determining the number of samples (n) used is referring to the Slovin approach. From the results of calculating the number of samples used in this study, there were 98 respondents. The scale of data measurement in this study used a Likert scale. The data analysis technique used is instrument test, classical assumption test, multiple linear regression analysis, hypothesis testing and coefficient of determination test (R2). The results of the study show that (1) the reputation variable has a positive and significant effect on competitiveness, (2) the social media marketing variable has a positive and significant effect on competitiveness, and (3) the reputation and social media marketing variables simultaneously have a positive and significant effect on Santo Thomas Catholic University of Medan .